Problems of Plastic Industries in Basra Governorate - Ayoub Abbas Al Zuani, Researcher. Waleed; Abid Rashid Al Sherifi, Assist. Lect. Dr. Rashid (Basra studies journal, 2023)
The industry is one of the most important basic rules for economic activity, including the plastic industries, which are part of the chemical manufacturing industries. It is of great importance and its importance comes from its component that supplies the local market with the various plastic goods needs instead of importing them from abroad. It also employs number of manpower and thus contributes in improving their standard of living and contributing to the development of other economic sectors through the various products it provides to these sectors The plastic industries in Basra governorate face problems and came in varying proportions, as the problem of government support ranked first with a rate of (19.4%), then the problem of marketing ranked second with a rate of (14.8%), the problem of fuel and energy sources ranked third with a percentage of (14.3%), the problem of raw materials ranked fourth with a percentage of (11.8%) and the problem of working people ranked fifth with a rate of (9.9%), then the problem of commercial fraud ranked sixth with a rate of (8.3%), while the problem of environmental pollution ranked seventh with a rate of (7.6%), and the problem of technological backwardness came in the eighth rank, with a percentage of ( 7%), and finally, the water problem ranked ninth with a rate of (6.2%).